MANAJEMEN PARTISIPATIF DALAM PELAKSANAAN PROGRAM PEMBERDAYAAN MASYARAKAT DI DESA SEA TUMPENGAN KECAMATAN PINELENG KAB. MINAHASA - LANTANG, ANGGI PRATAMA; TULUSAN, FEMMY; LALOMA, ALDEN (Sam Ratulangi University, 2022)
National and regional development is an inseparable part of village development activities,considering that the concentration of the population is still dominant in rural areas, so that the village isthe basis of socio-economic and political power that needs serious attention from the government. The maingoal of development carried out by the government is to improve the standard of living of its people. Variousbusinesses from various sectors continue to be developed in an effort to achieve these goals. In Law number6 of 2014 concerning Villages it is stated that village development is an effort to improve the quality of lifeand life for the greatest welfare of the village community. Therefore, community participation indevelopment is very important, without community participation, development only makes the communityas an object. In the implementation of community empowerment programs, the criteria used to measureparticipatory management are described by George E. Terry which includes planning, organizing,mobilizing, and supervising.Keywords: Participatory Management, Community Empowerment